MENINGKATKAN HASIL BELAJAR MELALUI MODEL PEMBELAJARAN TWO STAY TWO STRAY (TSTS) PADA MATA PELAJARAN IPS PESERTA DIDIK KELAS IV DI SDN 4 TELAGA KABUPATEN GORONTALO - Abd. Hamid Isa; Amna Noho; Irawaty Ahmad (Jurnal Ilmu Pendidikan UMGo, 2024)
The purpose of this research is to improve student learning outcomes through the use of the two stay two stray (TSTS) learning model in social studies subjects for class IV SDN 4 Telaga, Gorontalo Regency. This type of research is classroom action research (CAR), because this research is a form of reflective study by the perpetrators of the action. This research uses the Kemnis and Taggart models with the research subjects that will be used in the implementation of this classroom action research are fourth grade students at SDN 4 Telaga, Gorontalo Regency, totaling 28 students, consisting of 19 male students, and 9 female students. Data collection techniques used (1) observation, (2) interview guidelines, (3) tests and (4) documentation. Indicators of student success with completeness criteria (KKM) are 75 and classical completeness of 85%. The results showed the Two Stay Two Stray (TSTS) learning model could improve the learning outcomes of class IV students at SDN 4 Telaga, Gorontalo Regency. The results of the initial observation, total completeness 26%, in the first cycle increased to 61% an increase in the second cycle 92.85%. In this action, the learning outcomes of students increase until they reach the specified completeness criteria